Involvement of 5-HT3 and 5-HT4 Receptors in the Regulation of Circadian Clock Gene Expression in Mouse Small Intestine - Natsumi Aoki; Hiroyuki Watanabe; Kazuya Okada; Kazuyuki Aoki; Takuma Imanishi; Daisuke Yoshida; Ryosuke Ishikawa; Shigenobu Shibata (Elsevier, 2014)
Several lines of evidence suggest that 5-HT receptors play a critical role in the expression of clock genes in the suprachiasmatic nucleus, the main circadian oscillator in hamsters. The contributions of 5-HT-receptor subtypes in the intestine, where they are expressed at high concentrations, are however not yet clarified. The 5-HT synthesis inhibitor, p-chlorophenylalanine, attenuated the daily rhythm of Per1 and Per2 gene expression in the intestine. Injection of 5-HT and agonists of the 5-HT3 and 5-HT4 receptors increased Per1/Per2 expression and decreased Bmal1 expression in a dose-dependent manner. Although treatment with antagonists of 5-HT3 and 5-HT4 alone did not affect clock gene expression, co-injection of these antagonists with 5-HT blocked the 5-HT-induced changes in clock gene expression. Increased tissue levels of 5-HT due to treatment with the antidepressants clomipramine and fluvoxamine did not affect clock gene expression. The present results suggest that the 5-HT system in the small intestine may play a critical role in regulating circadian rhythms through 5-HT3/5-HT4-receptor activation. Keywords:: circadian clock, serotonin, intestine, 5-HT3, 5-HT4